Goal change and goal achievement for emerging adults across the pilot FAMS-T1D intervention for type 1 diabetes - Berg, Cynthia A.; Mansfield, Jessica H.; Boggess, Silas B.; Martin, Julia V.; Creer, Benjamin; Peck, Torri K.; Wiebe, Deborah J.; Butner, Jonathan E.; Mayberry, Lindsay S. (Frontiers in Clinical Diabetes and Healthcare, 2024)
ObjectiveInterventions for emerging adults (EAs) with type 1 diabetes (T1D) focus on goal setting, but little is known about how goal achievement relates to intervention outcomes. We examined how goals change, how goal achievement relates to diabetes outcomes, and identified barriers and facilitators to goal achievement.MethodEAs with T1D (N=29, M age=21.6 years, 57% female) were coached monthly to set a behavioral goal across a 3-month feasibility trial. Coaching notes were qualitatively coded regarding type, complexity, and changes in goals. Goal achievement was measured via daily responses to texts. HbA1c, self-efficacy, diabetes distress, and self-care were assessed pre- and post-intervention.ResultsEAs frequently set food goals (79%) in combination with other goals. EAs overwhelmingly changed their goals (90%), with most increasing goal complexity. Goal achievement was high (79% of days) and not affected by goal change or goal complexity. Goal achievement was associated with increases in self-efficacy and self-care across time. Qualitative themes revealed that aspects of self-regulation and social-regulation were important for goal achievement.ConclusionMeeting daily diabetes goals may enhance self-efficacy and self-care for diabetes.Practice ImplicationsAssisting EAs to reduce self-regulation challenges and enhance social support for goals may lead to better diabetes outcomes.